Analisis Rasio Keuangan Dan Corporate Governance Dalam Memprediksi Financial Distress - Carina Agustina; Augustpaosa Nariman (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims at how the role of financial ratio such as profitability, leverage, liquidity, cash flow ratio, and corporate governance on financial distress in manufacture industry listed on the Indonesia Stock Exchange during 2017-2019. Sample was selected using purposive sampling method and the valid data was 118 companies. Data processing techniques using logistic regression what helped by Eviews 11. The result of this research showed that profitability and liquidity does not have significant effect on financial distress, while leverage, corporate governance and cash flow ratio have a significant effect on financial distress. The implication of this research is to find out the condition of the company and to improve the condition of the company if it is in a critical condition.